Relationship Between Smoking Status and Walk Distance at The 6 Minute Walk Test in Pilgrims Applicant at The Cardiac Rehabilitation Division of Dr. Saiful Anwar Hospital Malang June 2017 - T Adriyanto (ACI (Acta Cardiologia Indonesiana), 2017)
Objective: To find out the correlation between smoking status and distance of 6-minute walk .....